2003
DOI: 10.1002/ajmg.a.20151
|View full text |Cite
|
Sign up to set email alerts
|

First‐year mortality rates for selected birth defects, Hawaii, 1986–1999

Abstract: Birth defects have been the leading cause of infant death in the United States for over the last decade. However, there is little population-based data on the first-year mortality rates for many specific birth defects and the factors that may affect these mortality rates. This investigation examined the first-year mortality rates for 54 selected birth defects of various organ systems in Hawaii during 1986-1999 using data from a population-based birth defects registry and evaluated the impact of the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
41
1
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 33 publications
3
41
1
4
Order By: Relevance
“…This effect of multiple congenital anomalies on survival has been described in other population-based studies of birth defects. 2,8,15,16 Racial/ethnic disparities in survival were found in the present study, as reported by others. After multivariable adjustment, NH blacks with functional single ventricle had a 41% greater risk of death compared with NH whites.…”
Section: Fixler Et Al Five-year Mortality Of Functional Single Ventriclesupporting
confidence: 90%
See 3 more Smart Citations
“…This effect of multiple congenital anomalies on survival has been described in other population-based studies of birth defects. 2,8,15,16 Racial/ethnic disparities in survival were found in the present study, as reported by others. After multivariable adjustment, NH blacks with functional single ventricle had a 41% greater risk of death compared with NH whites.…”
Section: Fixler Et Al Five-year Mortality Of Functional Single Ventriclesupporting
confidence: 90%
“…4 -7 Furthermore, prior published population-based studies have the limitation of using broadly defined heart defect groups and reporting survival of cases born Ͼ10 years ago. [1][2][3] The strengths of our study rest on it being population based, having carefully edited specific diagnostic categories, having births from a more recent era (1996 to 2003), and having follow-up to 5 years of age. Survival of these infants with functional single ventricle was significantly less than that of infants with d-transposition requiring neonatal arterial switch surgery.…”
Section: Fixler Et Al Five-year Mortality Of Functional Single Ventriclementioning
confidence: 99%
See 2 more Smart Citations
“…De haber crecido esta a la par de la capacidad diagnós-tica, se habría observado un aumento en la supervivencia de los infantes con MC graves y se habría detenido -o incluso invertido-la tendencia creciente de las TMIe por MC graves. Así ha ocurrido en los países con mayor renta per cápita (18,19), pero no en los de Amé-rica Latina y de Europa Oriental (20), lo que sugiere que este renglón de la atención infantil es sensible a la magnitud de la inversión en salud.…”
unclassified